2021
DOI: 10.1111/sum.12744
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics from surface‐applied organic matter amendments on no‐till orchard soil

Abstract: Advancing conservation agriculture depends on understanding nutrient dynamics of organic matter amendments (OMA) on no‐till soil. This field incubation study compared surface‐applied composted dairy manure (CM), green waste compost (GWC) and an unamended control from March to September in 2015 and 2016 using a RCBD in a California almond (Prunus dulcis) orchard. Measurements included OMA nutrient release rates, changes in soil organic carbon (SOC), total N (TN) and inorganic N, P and K availability using in‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…The site conditions and historical management may also contribute to the utility and ecosystem services of amendments ( De Leijster et al., 2019 ) since compost applications increased OM in the replant location, but not the virgin location compared to the control. Nevertheless, increasing OM in the replant location after only several years agrees with other studies which have observed increased soil organic carbon after adding OM amendments to the soil surface ( Villa et al., 2021 ; Khalsa et al., 2022 ). On the other hand, more than four years may be necessary to observe changes to OM or tree parameters when using amendments ( Neilsen et al., 2014 ; Toselli et al., 2019 ) and the four-year duration of this study is insufficient to understand the treatment effects over the lifetime of the orchard.…”
Section: Discussionsupporting
confidence: 91%
“…The site conditions and historical management may also contribute to the utility and ecosystem services of amendments ( De Leijster et al., 2019 ) since compost applications increased OM in the replant location, but not the virgin location compared to the control. Nevertheless, increasing OM in the replant location after only several years agrees with other studies which have observed increased soil organic carbon after adding OM amendments to the soil surface ( Villa et al., 2021 ; Khalsa et al., 2022 ). On the other hand, more than four years may be necessary to observe changes to OM or tree parameters when using amendments ( Neilsen et al., 2014 ; Toselli et al., 2019 ) and the four-year duration of this study is insufficient to understand the treatment effects over the lifetime of the orchard.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the compost-amended orchard soil had ∼61% higher total C content and 63% higher total N content than the No Compost treatment (Table 1). This increase in total C and N aligns with other findings on effects of OM amendments, such as composted dairy manure, chicken litter, and yard green waste, in almond and peach orchards (Khalsa et al, 2022;Martínez-Blanco et al, 2013;Preusch & Tworkoski, 2003). Soil bulk density tended to be lower in our compost amended orchard soils (Table 1), which is consistent with previous work showing that organic amendments reduce bulk density and compaction (Arvanitoyannis & Kassaveti, 2007;Cayuela et al, 2004;Mujdecİ, 2011;Peck et al, 2011).…”
Section: Effects Of Compost On Soil Attributes Soil Water Content And...supporting
confidence: 92%
“…In the current study, we posit that the reduced N 2 O emissions associated with increased soil C in compost may be a result of increased microbial immobilization of available N (Khalsa et al, 2020(Khalsa et al, , 2022Senbayram et al, 2012). We examine this supposition here.…”
Section: Composting and Fertigation Effects On Substrate Availability...mentioning
confidence: 83%
See 2 more Smart Citations